Costs and Benefits of Audit Quality in the IPO Market: A Self-Selection Analysis - Hogan, Chris E. (The Accounting Review, 1997)
[This study examines the trade-offs that an entrepreneur makes in an initial public stock offering (IPO) between the incremental costs and benefits of selecting a Big 6 audit firm. The benefit of hiring a Big 6 auditor is assumed to be reduced underpricing, consistent with Beatty (1989) and Balvers et al. (1988). The cost of hiring a Big 6 auditor is higher auditor compensation. Evidence drawn from a sample of IPOs during the early 1990s is consistent with a differentiated market for audit services where owners select the type of auditor that minimizes the sum of underpricing and auditor compensation costs.]